2011
DOI: 10.1542/neo.12-4-e198
|View full text |Cite
|
Sign up to set email alerts
|

Preeclampsia: Effect on the Fetus and Newborn

Abstract: Preeclampsia (PE) is the most common medical complication in pregnancy and a major cause of maternal and fetal morbidity and mortality. This disease is a great challenge for obstetricians because there are no effective interventions to treat or prevent it, and antenatal care involves a difficult balance between the risks for women to continue pregnancy and the risks for the baby's early birth. Fetal complications in PE are directly related to gestational age and the severity of maternal disease and include inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
24
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 45 publications
0
24
0
Order By: Relevance
“…Intrauterine growth restriction is a common complication of hypertensive disorders of pregnancy, and a high incidence of small for gestational age infants in preeclamptic women has been reported, ranging from 15% to more than 50% (1). This was confirmed in our study, in which 44% of premature infants of hypertensive mothers were small for gestational age.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Intrauterine growth restriction is a common complication of hypertensive disorders of pregnancy, and a high incidence of small for gestational age infants in preeclamptic women has been reported, ranging from 15% to more than 50% (1). This was confirmed in our study, in which 44% of premature infants of hypertensive mothers were small for gestational age.…”
Section: Discussionmentioning
confidence: 99%
“…The consequences of these disorders in the infant most notably include intrauterine growth restriction, prematurity, and increased risk of neonatal diseases (1). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results expand upon previous findings that maternal gestational hypertension was associated with an increase in behavioral problems in offspring, 1 poorer verbal ability at age 10 years, 2 and adverse developmental outcomes at 4.5 years 5 by demonstrating that effects are present in infancy. 8 Although a controlled trial of antihypertensive medications (methyldopa and labetalol) did not show adverse effects for the fetus, 34 such medications have since been implicated in later mental health problems for children. 32 This is the earliest report of behavioral difficulties after pregnancy complicated by gestational hypertension and/or preeclampsia.…”
Section: Discussionmentioning
confidence: 99%
“…4 Another recent study found that severe early-onset hypertensive complications of pregnancy, including preeclampsia and HELLP syndrome (hemolysis, elevated liver enzymes, and low platelet count), were associated with abnormal developmental outcomes (e.g., cognition, motor development) at age 4.5 years, but that study found no link between gestational hypertension and child behavior. 8 Alternatively, it is possible that these findings may reflect side effects of the drugs used to treat maternal gestational hypertension and preeclampsia, such as methyldopa and labetalol. This could be because of psychoneuroendocrine changes directly and indirectly associated with gestational hypertension and preeclampsia.…”
mentioning
confidence: 99%